2018
DOI: 10.1161/hypertensionaha.117.10296
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing Reveals a Monogenic Cause of Disease in ≈43% of 35 Families With Midaortic Syndrome

Abstract: Midaortic syndrome (MAS) is a rare cause of severe childhood hypertension characterized by narrowing of the abdominal aorta in children and is associated with extensive vascular disease. It may occur as part of a genetic syndrome, such as neurofibromatosis, or as consequence of a pathological inflammatory disease. However, most cases are considered idiopathic. We hypothesized that in a high percentage of these patients, a monogenic cause of disease may be detected by evaluating whole exome sequencing data for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Whole-exome sequencing studies revealed that protein truncating mutations (splice site and frameshift mutations) in NF1 may result in MAS. 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whole-exome sequencing studies revealed that protein truncating mutations (splice site and frameshift mutations) in NF1 may result in MAS. 16 …”
Section: Discussionmentioning
confidence: 99%
“…NF1 is the most common genetic disorder associated with MAS and encountered for 5–22% of the cases. 1 , 3 , 6 , 7 , 16 , 17 , 19 Another study found NF1 as the second cause of MAS after Williams syndrome. 3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study had characterized genetic contributors to the etiology of midaortic syndrome, reporting a genetic cause in almost half of children with midaortic syndrome. [10] We therefore hypothesized that there would also be a substantial genetic contribution to pediatric renovascular hypertension in general. We performed whole exome sequencing (WES) in our patient cohort, aiming to identify known causes as well as discover potentially novel ones.…”
Section: Introductionmentioning
confidence: 99%